2020
DOI: 10.1073/pnas.1920039117
|View full text |Cite
|
Sign up to set email alerts
|

High-speed interferometric imaging reveals dynamics of neuronal deformation during the action potential

Abstract: Neurons undergo nanometer-scale deformations during action potentials, and the underlying mechanism has been actively debated for decades. Previous observations were limited to a single spot or the cell boundary, while movement across the entire neuron during the action potential remained unclear. Here we report full-field imaging of cellular deformations accompanying the action potential in mammalian neuron somas (−1.8 to 1.4 nm) and neurites (−0.7 to 0.9 nm), using high-speed quantitative phase imaging with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 55 publications
1
57
1
Order By: Relevance
“…Full-field imaging of primary neuronal cultures isolated from rat cortical tissues during an action potential was performed using high-speed quantitative phase imaging by Ling. et al [ 158 ]. This technique enables 0.1 ms temporal resolution and an axial path length sensitivity of 4 pm per pixel.…”
Section: Potentials Across Membranesmentioning
confidence: 99%
“…Full-field imaging of primary neuronal cultures isolated from rat cortical tissues during an action potential was performed using high-speed quantitative phase imaging by Ling. et al [ 158 ]. This technique enables 0.1 ms temporal resolution and an axial path length sensitivity of 4 pm per pixel.…”
Section: Potentials Across Membranesmentioning
confidence: 99%
“…In general, the physiological processes associated with neural activity affect the cell's refractive index (9) and shape (10,11), which together alter light propagation, including changes in light scatter ing (12,13), polarization (14), and optical path length (OPL) (5). Similarly, cellular deformations accompanying the transmembrane voltage change during action potentials have been documented in crustacean nerves (15), squid giant axons (16), and mammalian neurons (11,17). Interferometric imaging of these changes, in general, and cellular deformations associated with variations in the cell potential, in particular, offer a noninvasive labelfree optical approach to monitor the electrical activity in neurons (10).…”
Section: Introductionmentioning
confidence: 99%
“…Using atomic force microscopy, Zhang et al (21) demonstrated that human embryonic kidney (HEK) 293 cells deformed proportionally to the membrane potential change (1 nm per 100 mV). Using quan titative phase microscopy, Ling et al (10) demonstrated cellular deformations of up to 3 nm during the action potential in spiking HEK293 cells and about 1 nm in mammalian neurons (11). Detect ing the millisecondfast and nanometerscale cellular deformations in transmission is very challenging because of the OPL difference between the cells and the surrounding medium scales with the refractive index difference, which is only ≈0.02.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the mid-IR photothermal process, PDI can fertilize research related to imaging of short lifetime events that includes but not limits to visible, near-infrared, and other transient physical perturbations 46,47 . Lock-in free PDI offers nanoseconds temporal resolution that is ultimately limited by the photon detector response.…”
Section: Discussionmentioning
confidence: 99%